An Evaluation of Oral Midazolam for Anxiety and Pain in First-Trimester Surgical Abortion: A Randomized Controlled Trial. Issue 1 (July 2015) - Bayer, Lisa L.; Edelman, Alison B.; Fu, Rongwei; Lambert, William E.; Nichols, Mark D.; Bednarek, Paula H.; Miller, Kelsey; Jensen, Jeffrey T.
Abstract : OBJECTIVE: To estimate the effect of oral midazolam on patient pain and anxiety perception during first-trimester surgical abortion. METHODS: Between May and December 2013, we conducted a randomized, double-blind, placebo-controlled trial. Patients between 6 0/7 and 10 6/7 weeks of gestation received 10 mg oral midazolam or placebo 30–60 minutes before surgical abortion. All patients received ibuprofen and a paracervical block. We powered the study (power=80%; significance level=.025) to detect a 15-mm difference in our two a priori primary outcomes of pain and anxiety with uterine aspiration on a 100-mm visual analog scale. Secondary outcomes were pain and anxiety at additional time points, memory, satisfaction, side effects, and adverse events. RESULTS: Demographics were similar between groups (placebo=62, midazolam=62). Compared with those randomized to placebo, patients who received midazolam had significantly less anxiety preoperatively (room entry: 51.4 mm compared with 34.5 mm, P <.001; positioning: 56.6 mm compared with 45.4 mm, P =.02). There was no difference in pain ( P =.28) or anxiety ( P =.14) during uterine aspiration or at other procedural time points. A significantly greater number of patients in the midazolam group reported partial amnesia (31/61 compared with 16/61, P =.005) and dizziness (30/61 compared with 18/61, P =.03). Controlling for baseline differences, patients who received midazolam reported more postoperative sleepiness ( P <.001) and less postoperative nausea ( P =.004). There was no difference in overall satisfaction ( P =.88). CONCLUSION: Although oral midazolam reduces preprocedural anxiety, it does not reduce pain or anxiety with uterine aspiration during first-trimester surgical abortions. CLINICAL TRIAL REGISTRATION: ClinicalTrials.gov, www.clinicaltrials.gov, NCT01830881. LEVEL OF EVIDENCE: I Abstract : Oral midazolam does not reduce pain or anxiety with uterine aspiration during first-trimester surgical abortion, but it reduces preprocedural anxiety.